Physiological improvement to enhance Escherichia coli cell-surface display via reducing extracytoplasmic stress - Narayanan, N.; Chou, C. P. (Biotechnology Progress, 2008)
Cell physiology was impaired when enhanced yellow fluorescence protein (EYFP) was displayed on the Escherichia coli cell surface, resulting in growth arrest and poor display performance. Coexpression of Skp, a periplasmic chaperone known to interact with several outer membrane proteins for their transport and insertion in the outer membrane, was demonstrated to be effective to restore cell physiology. When Skp was coexpressed with EYFP display, host cells became less sensitive to ethylenediaminetetraacetic acid and sodium dodecyl sulfate, implying that cell physiology was improved. Most importantly, the display performance was highly enhanced as a result of the increased specific fluorescence intensity without growth arrest. The results of transmission electron microscopy indicate that the density of surface-displayed EYFP was highly increased upon Skp coexpression. Cells with EYFP display experienced extracytoplasmic stress, as reflected by the induced promoter activities of three stress-responsive genes, degP, CPXP, and rpoH. The extracytoplasmic stress reflected by the degP promoter activity appears to be consistent with the cell physiology observed phenotypically under various culture conditions for cell-surface display. Therefore, the P-degP::lacZ allele was proposed to be a suitable "sensor" for monitoring the extracytoplasmic stress and cell physiology during the course of E. coli cell-surface display.